Smart On-Site Immobilizable Near-Infrared II Fluorescent Nanoprobes for Ultra-Long-Term Imaging-Guided Tumor Surgery and Photothermal Therapy - Zhang, Yuqi; Zhao, Meng; Fang, Jing; Ye, Shuyue; Wang, Anna; Zhao, Yan; Cui, Chaoxiang; He, Lei; Shi, Haibin (ACS applied materials & interfaces, 2021)
Accurate diagnosis and efficient treatment of tumors are highly significant in battling cancer. Near-infrared II (NIR-II) fluorescence imaging shows big promise for deep tumor visualization in living systems due to high temporal and spatial resolution and deep tissue penetration capability, whereas the development of efficient NIR-II probes for tumor theranostics still faces a huge challenge. Herein, we have designed and constructed intelligent mPEG5000–PCL3000-encapsulated NIR-II nanoprobe ZM1068-NPs that showed great chemical stability and excellent biocompatibility. With the merits of the strong fluorescence in the NIR-II region and prominent optical-thermal conversion efficiency, this probe was successfully used for NIR-II imaging-guided surgery and photothermal therapy of breast carcinoma in living mice. More notably, it was for the first time found that ZM1068 dyes could be covalently on-site-immobilized within tumors through the thiol–chlor nucleophilic substitution reaction, resulting in improved tumor accumulation and retention time. We thus envision that this probe may provide an attractive means for precise cancer diagnosis and treatment.